Design and construction of three-dimensional lightweight timber grid structures explored through a mass-customised approach - Larsen, Olga Popovic (Mass Customisation and Personalisation in Architecture and Construction, 2013)
Mass customisation has successfully been applied in the product industries and in recent years is also finding application in the built environment. Examples of how to enhance the building processes and architectural practice by applying mass-customisation principles are becoming more evident. We are starting to see architectural examples where facade elements have been mass-customised and as a result we have solutions that are constructed to a higher specification within comparable budgets. Also this method offers possibilities of a more integrated design/build approach with possibilities for better and more appropriate use of materials, construction methods and processes. Sustainable design/ production processes become more easily applied without compromising the architectural qualities. However, as a result of the manually operated and craft nature of the building industry, mass customisation within the built environment is still only applicable in some cases where industrialised approaches to design/production have been used. This chapter discusses the architectural potential and design/construction opportunities that lightweight timber grid load-bearing roof structures can offer. A case study with two lightweight timber structures involving the construction of two full-scale physical models - a gridshell and a multiple reciprocal frame structure - is presented in the context of mass customisation.